MENTAL REENGINEERING THOUGH COMMUNITY DEVELOPMENT PRACTICE FOR FLOOD MITIGATION IN BAYELSA STATE NIGERIA - Owede, Kosioma E (Top Educational Review Journal (TERJ), 2025)
Flooding is a recurring natural disaster in Nigeria, resulting in significant human, material, and economic losses. Although infrastructural measures are essential, they are often insufficient to mitigate the psychological trauma and distress caused by flooding. This article explores the potential of community development initiatives to promote mental engineering as a resilience strategy against flooding in Nigeria. This article examines the nexus between community development projects/programmes and psychosocial wellbeing, coping mechanisms and flood risk perception. This highlights the critical role of community development in fostering mental resilience, promoting collective efficacy, and enhancing flood risk management. The paper concludes by emphasising the need for a holistic approach to flood risk management, integrating community leadership into community development practice, mental engineering, and infrastructural measures to promote sustainable resilience in flood-prone communities.